Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/nuka-2015-0115
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Chalmers Grouped Actinide Extraction Process

Abstract: Abstract. Several solvents for Grouped ActiNide EXtraction (GANEX) processes have been investigated at Chalmers University of Technology in recent years. Four different GANEX solvents; cyclo-GANEX (CyMe 4 --BTBP, 30 vol.% tri-butyl phosphate (TBP) and cyclohexanone), DEHBA-GANEX (CyMe 4 -BTBP, 20 vol.% N,N-di-2(ethylhexyl) butyramide (DEHBA) and cyclohexanone), hexanol-GANEX (CyMe 4 -BTBP, 30 vol.% TBP and hexanol) and FS-13-GANEX (CyMe 4 -BTBP, 30 vol.% TBP and phenyl trifl uoromethyl sulfone (FS-13)) have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Comparing these distribution ratios with previously investigated GANEX systems using other diluents, it is found that the values are found to be in a similar order of magnitude. [30][31][32] Desirable distribution ratios should render a high metal extraction, while still maintaining a feasible actinide stripping. Neptunium has a rather low distribution ratio, and therefore further investigations are needed to successfully extract neptunium together with the other actinides in this system.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing these distribution ratios with previously investigated GANEX systems using other diluents, it is found that the values are found to be in a similar order of magnitude. [30][31][32] Desirable distribution ratios should render a high metal extraction, while still maintaining a feasible actinide stripping. Neptunium has a rather low distribution ratio, and therefore further investigations are needed to successfully extract neptunium together with the other actinides in this system.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, F-3 ( meta -nitrobenzotrifluoride) or FS-13 (phenyltrifluoromethylsulfone)aromatic polar diluents with low viscosity, high density, and good chemical stabilitymay be listed. In addition to other advantages, their high density ensures good phase separation during metal extraction . A new group of these polar fluorinated diluents includes carbonates of fluorinated alcohols, for example, BK-1 (carbonate of 2,2,3,3-tetrafluoropropan-1-ol; Table ) or BK-2 (carbonate of 2,2,3,3,4,4,5,5-octafluoropentan-1-ol) .…”
Section: Introductionmentioning
confidence: 99%
“…The co-recovery of minor actinides is incorporated by introducing a second extracting agent that shows high selectivity for the minor actinides over FPs, including chemically similar lanthanides. For example, the CHALMEX concept [7][8][9] uses a solvent containing CyMe 4 -BTBP (6,6′bis(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzo-1,2,4-triazin-3-yl)-2,2′-bipyridine, Figure 1) [10][11] plus TBP dissolved in a polar diluent such as cyclohexanone or FS-13 (phenyl trifluoromethyl sulfone) to directly extract only U and TRU from dissolved fuel solutions. The chemical system has promise but so far has not been tested in a counter-current flow-sheet trial.…”
Section: Introductionmentioning
confidence: 99%